︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎ ︎︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎
︎ ︎ ︎ ︎ ︎ ︎
х²+1/х+1-1=0
х²+1/х+0=0 -> х²+1/х=0
По теореме Виета
ax² + bx + c = 0
x₁x₂=c/a
с=0, а=1, 0/1=0
ответ: x₁x₂= 0